Analyzing and quantifying security data through a geospatial visualization framework : empirical research regarding social and economic indicators in Portugal - Nascimento, Marcel Motta do (2019)
Dissertation proposal presented as partial requirement for obtaining the Master’s degree in Information Management, with a specialization in Business Intelligence and Knowledge Management